Recent progress in the development of catalysts for steam reforming of biomass tar model reaction - Ashok, Jangam; Dewangan, Nikita; Das, Sonali; Hongmanorom, Plaifa; Wai, Ming Hui; Tomishige, Keiichi; Kawi, Sibudjing (Fuel processing technology, 2020)
This review describes recent advances in development of catalysts for steam reforming of biomass tar model reactions, using toluene, benzene and naphthalene as tar model compounds. Catalytic systems have been categorized based on their catalytic properties. The material properties such as oxygen mobility and basicity of catalysts showed great influence in their effectiveness in tar reforming. Changes in the properties such as oxygen mobility and basicity with various metal and/or support modifications and their influence on catalytic behavior with respect to reactant conversion and coke inhibition is comprehensively discussed. The activity of the catalysts derived from various synthesis methods is also introduced. The changes induced in the pathways of steam reforming reactions by catalyst modification is also highlighted together with changes in catalytic properties. Reaction pathways for steam reforming of toluene by experimental studies together with insights gained from computational DFT studies is also presented. [Display omitted] •Recent developments in the catalyst technology for tar model reforming were reviewed.•Catalytic systems have been categorized based on their catalytic properties.•Modified Ni-based catalysts are much explored for tar model reforming reactions.•Biochar or minerals as catalyst supports are overlooked and provide good support for tar reforming.